Technical evaluation of inoculants in common bean with efficient Rhizobium strains in nitrogen fixation in Central America. - Acuña, Oscar (2006)
Atechnical evaluation trial was carried out to evaluate the use of inoculants in bean with efficient Rhizobium strains, in oder to obtain more information about the usefulness of this technology in the common bean production. The regional experiment was planted in 45 localities distributed in Costa Rica (20), Panama (10), Nicaragua (10) and El Salvador (5), during 1998 and 1999. The experiment included four treatments: 1. Control; 2. Inoculation; 3. Half of recommended fertilization plus inoculation; 4. Recommended fertilization (Fer Rec). The inoculant was prepared and distributed by the University of Costa Rica. The variety and the fertilization utilized in treatments 3 and 4, were the recommended in each locality. The experimental plot varied between 50 and 100 m2 and a randomized complete block design with three replications was used. Thirty-nine trials were harvested and the seed yield and production costs were registered. The analysis of variance by production areas and countries, used the yield average by location; the economic analysis used the partial budget methodology. The results showed that: a) the bean response to inoculation and/or fertilization, varied among places; b) the regional analysis indicated bean response to the inoculant utilization and in the 80% of the cases, the economic analysis selected the inoculation treatment as profit; c) with the exception of Panama, the use of half of recommended fertilization plus inoculation, was better than inoculation only.